Phytoparasitic nematodes associated with the cultivation of maize (Zea mais L.) in the regions of Puno and Cusco - Lima-Medina, Israel (2018)
Corn is a cereal of global importance for its different industrial uses and nutritional value; however, the effects caused by the presence of nematodes in the corn can be very harmful. For this reason, the present work was proposed with the main objective of recognizing and identifying the parasitic plants nematodes associated with this crop in the regions of Puno and Cusco; For this purpose, 131 soil samples were collected during the 2015-2016 campaign in the Puno Region (districts of Chupa, Sandia, San Juan del Oro, Cuyocuyo, Ayapata, Ollachea, and San Gabán); and 30 samples in the Cusco Region, (districts of Pisac and Urubamba). The soil samples were processed by the centrifugal fluctuation method in sucrose solution. After analyzing the samples, the results determine the presence of the following genera of nematodes: Helicotylenchus spp., Mesocriconema spp., Globodera spp., Xiphinema spp., Rotylenchus spp. Dorylaimus spp. and free-living nematodes. Reporting the presence of six genera associated with the cultivation of corn is of scientific interest, because it will allow continuing applied technical research.